Analysis of demographic processes of population settlement in the regions of Kazakhstan - Kireyeva А.; Bekturganova М.; Alzhanova Ф. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
Today in Kazakhstan there is inequality in the level and quality of life of the population, which is due to differences in natural conditions and resources, the specifics of settlement and the nature of the economic development of the territory, and geographical location. The purpose of the study is to analyze the current demographic situation, the system of conditions, factors and indicators of population reproduction and settlement in the regions of Kazakhstan. The study examines the problems of settlement, regional demography and migration in Kazakhstan, as well as disproportions in population density and fragmentation of space in different regions. The research work explores the possibility of solving these issues through modern trends and principles of effective development of regional economic systems. The research methodology is based on the position of methodological generalization and system analysis. The methodological basis of the study is a generalization of classical and modern theories of population distribution by region, theoretical developments of domestic and foreign scientists in the field of balanced territorial development, actual placement, population reproduction, increasing the competitiveness and sustainability of regions in the context of globalization and Industry 4.0. The study revealed that in the Republic of Kazakhstan, since 2013, significant changes have been taking place in the demographic situation, especially in the context of increasing internal migration processes in certain regions. These demographic and migration changes have a direct impact on the socio-economic well-being of regions, in particular by increasing the flow of human capital abroad. In addition, the spontaneous development of migration processes aggravates the imbalance of labor resources, which may cause additional social and economic problems in the future. The authors define rational population settlement as the main factor in managing and planning the economic development of the region.